Survivor's Debt - Pinkerton, Anne A (Ars Medica, 2020)
“Make a fist and hold it,” the friendly young nurse says to me as she pumps up the blood pressure cuff. It tightens around my bicep, and she slides a needle into my rising vein. When she does the same to my other arm, I smile up at her in her bright red scrubs realizing that the Red Cross staff members no longer say things like, “OK, you’ll feel a little sting” or ask if I’m ready. They know that I know the drill. On the first anniversary of my brother David’s death, now nearly ten years ago, I decided to give blood for the first time at a local donation drive. David had been a doctor, and I figured he’d have appreciated my tribute.